Síntese, Caracterização, Estudo Computacional e Atividade Biológica do Complexo Binuclear de Cobre(II) com Fenantrolina e Ácido Maleico - SIMPLICIO, Jad Lorena Feitosa (2024)
The aim of this work was to synthesize a crystal of a binuclear copper(II) complex with the ligands 1,10-phenanthroline (Phen) and maleic acid (Mal) [Cu2(Fen)2(Mal)2]2H2O•CH3OH. The structural, vibrational, electronic, thermal and biological properties of the material were studied. The material was synthesized using the slow solvent evaporation method from a mixed saturated solution of water and methanol in equimolar proportion. The crystal was characterized by powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FT-IR), Raman spectroscopy at room temperature, thermal TG/DTA and DSC, ultraviolet-visible spectroscopy (UV-Vis) and biological tests. In addition, theoretical calculations based on density functional theory (DFT) were carried out on the complex to obtain the chemical reactivity descriptors, frontier orbitals, electrostatic potential map, thermochemical parameters and IR and Raman vibrational modes in vacuum, water, methanol and in the solvent mixture (water and methanol). The XRD results showed that the binuclear crystal has a monoclinic system (space group C2/c (𝐶2ℎ 6 )), containing four formates per unit cell (Z = 4). DFT calculations using the PBE1PBE functional showed that the spin multiplicity in the triplet state is in better agreement with the experimental atomic distances and angles, providing a better geometric description and being easier to complex and optimize. The nucleophilic and electrophilic regions of the complex were observed from the electrostatic potential map. The energy calculations of the frontier molecular orbitals and the global reactivity indices showed that the complex is stable. From DFT calculations considering the solvation effect, the absorption bands in the IR and Raman scattering were assigned, comparing them with the experimental data and observing some changes in the spectra. Thermal analysis shows that the material is stable up to 303 K, but above this point there is a loss of water molecules, degradation of the organic matter, and subsequently the remaining metal ions and carbon compounds undergo partial oxidation. The calorimetry curve showed an enthalpy of vaporization of 114.41 kJ/mol, which is the enthalpy of vaporization of the two water molecules and one methanol present in the crystal. UV-Vis analysis showed that the complex exhibits molar absorptivity at a wavelength of 646 nm and identified the characteristic bands of d-d transitions for Cu(II). Finally, the biological tests of cell viability (MCF-7, MDA-MB-231 and HeLa cell lines) and bactericide (gram-positive and gram-negative bacteria) in vitro confirmed that the binuclear complex [Cu2(Fen)2(Mal)2]2H2O•CH3OH presents efficient results, making it a promising candidate for commercialization in the chemical industry.